The new SAAO infrared photometric standards based on the E regions - Carter, Brian Stuart (Department of Astronomy, 2016)
Since 1974, when the Glass standards were published, four other infrared groups have been set up at the other main southern observatories, i.e. the two Australian observatories, Mount Stromlo and Siding Spring Observatory CMSO) and Anglo-Australian Observatory (AAO) and the two observatories in Chile, European Southern Observatory (ESO) and the Cerro Tololo Inter-American Observatory (which uses the California Institute of Technology standard system) (CIT). Unfortunately there has been a serious lack of conformity. Each group has used a different set of filters and has different zero points. No standards are common to all the groups and only a few are in common between any of the systems. Several transformat1ons between the various systems have recently been published (Elias et al 1983 and Glass 1983) but the large errors in the transformation equations show the need for more accurate standard stars. Therefore, on the surface, the introduction by us of a new set of standards would appear in danger of adding confusion to the issue, but this is not, in fact, the case. Firstly, the new set is basically the same system as tha Glass standards but with greatly increased accuracy. Secondly, the work involved has shown up several anomalies and inaccuracies in other systems. Thirdly, this work has shown why such large errors are apparent when comparing the various sets of standards and where the causes probably lie. The observations for these new standards were started in August 1979. The standards were introduced at the SAAO at the beginning of March 1984. The set is likely to evolve with time, increase in number of stars and improve in accuracy.